Etika Interaksi Digital dalam Al-Qur’an: Analisis Tafsir Maudhu’i - Nurul Khaidah; Nur Aisah Simamora (Kartika: Jurnal Studi Keislaman, 2026)
The transformation of communication from physical to digital spaces has expanded opportunities for interaction while creating ethical problems, including misinformation, cyberbullying, privacy violations, and communication leading to sexual exploitation. This study aims to formulate principles of digital interaction ethics based on the Qur’an and explain their relevance to the characteristics of communication in cyberspace. It employs a qualitative library research design using the thematic interpretation method. The primary data consist of Qur’anic verses concerning verification of information, intrusion into privacy, backbiting, control of the gaze, prohibition of approaching adultery, and accountability for speech. Secondary data were obtained from Qur’anic commentaries and literature on digital communication and cyberpsychology. The data were examined through content and comparative analyses. The findings show that Qur’anic digital ethics rest on information verification, respect for privacy, prevention of cyberbullying, control of visual and sexual interactions, and awareness that every digital expression carries moral responsibility. Although digital interaction differs from face-to-face communication in anonymity, speed, and reach, the change of medium does not remove users’ ethical obligations. These findings underline the importance of developing digital literacy grounded in Qur’anic values